2022
DOI: 10.1021/acsanm.2c02957
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Fabrication of Ice-Templated Pure Polypyrrole Nanoparticle Hydrogels for High-Rate Supercapacitors

Abstract: Conducting polymer hydrogels with high conductivity, excellent electroactivity, and good mechanical strength are desirable for the design of highperformance energy storage devices. However, they suffer from the issue of low porosity, which hinders electrolyte diffusion and leads to poor rate performance. In this work, we developed a one-step, in situ chemical polymerization approach to fabricate a porous pure polypyrrole hydrogel (PPH) with a desirable nanostructure via an ice-templating strategy. This simple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…[ 10,52 ] The porous composite nanostructure with proper redox‐active polymer distribution can promote electron transfer and electrolyte diffusion, realizing large specific capacitance and excellent rate performance. [ 13,26,53 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10,52 ] The porous composite nanostructure with proper redox‐active polymer distribution can promote electron transfer and electrolyte diffusion, realizing large specific capacitance and excellent rate performance. [ 13,26,53 ]…”
Section: Resultsmentioning
confidence: 99%
“…[10,52] The porous composite nanostructure with proper redox-active polymer distribution can promote electron transfer and electrolyte diffusion, realizing large specific capacitance and excellent rate performance. [13,26,53] In PRH composite, self-assembled graphene sheets form a porous conductive matrix (Figure 5b), facilitating the electron transport between highly homogeneous PPAAB and the RGO substrate and improving ion diffusion in the electrode. Thus, PPAAB can significantly contribute to high capacitance and achieve excellent rate capability.…”
Section: Resultsmentioning
confidence: 99%
“…55 The proposed single vacancy-defect endohedral metallofullerenesuperhalogen registered also a notable optical nonlinearity response compared to a series of triangular nanorings, by incorporating B-/N doped phenalenyl (B/NPLY) into cycloparaphenylene (B n N 3Àn -CPLY 3 (n = 0, 1, 2, 3)). 56 It is found that the b tot values of the supramolecular complexes are between 1.17 Â 10 3 and 2.44 Â 10 4 a.u. for B 3 -CPLY 3 @C60, B 2 N-CPLY 3 @C60, CPLY 3 @C60 and N 3 -CPLY 3 @C60, compared to 3.8 Â 10 4 and 6.44 Â 10 6 a.u.…”
Section: Controlling Optical Nonlinearity: Static and Dynamic (Hyper)...mentioning
confidence: 98%
“…The morphology and porous structure of the electrode have a more significant impact on the electrochemical performance at higher rates. The gravimetric specific capacitance of the as-obtained CNF-PAA/PPy electrodes was found to be higher than that of other porous hydrogel electrodes with PPy reported in the literature, such as crosslinked PAAm filled with carboxymethylcellulose (CMC)/PPy (~140 F/g at 0.5 A/g) [73], a carboxylated CNF/PPy film electrode (~180 F/g at 0.5 A/g) [74], a CMC-PANI/carbon nanotube film electrode (348.8 F/g at 0.5 A/g) [75], and a porous, pure polypyrrole hydrogel prepared via the ice-templating method (265 F/g at 1.35 A/g) [76]. This comparison demonstrates the possible practical interest in electrodes based on colloid brushes.…”
Section: The Morphology and Electrochemical Performance Of The Electr...mentioning
confidence: 99%